Gender Inequalities and the Effects of Feminine Artworks on Public Spaces: A Dialogue - Alizadeh, Hooshmand (Social Inclusion, 2021)
Feminist street art aims to transform patriarchal spaces into places of gendered resistance by asserting a feminist presence in the city. Considering this, as well as women’s social life, their struggle against lingering forces of patriarchy, and relating features of inequality (domestic violence), there was a feminist installation artwork by the young Kurdish artist Tara Abdulla that shook the city of Sulaimani in Iraqi Kurdistan on 26 October 2020. She had prepared a 4,800‐meter‐long washing line covered with the clothes of 99,678 Kurdish women who were survivors of sexual and gender‐based violence. They installed it along the busiest street of the city (Salim Street). She used this piece of feminine to express her reaction to the Kurdish society regarding, the abuse that goes on silently, behind closed doors. She also aimed towards normalizing women’s bodies. After the installation, she received many controversial reactions. As her artwork was a pioneering project in line with feminist issues in Kurdistan which preoccupied the city for quite a while, the aim of this article is to investigate the diverse effects of her work on the current dialogue regarding gender inequality in the Kurdish society. To do this, we used the research method of content analysis on big data (Facebook comments) to investigate the public reactions of a larger number of locals. The Feminine effectively exposed some of the deep‐rooted cultural, religious, and social barriers in addressing gender inequalities and silent sexual violence issues in the modern Kurdish patriarchal society.